STRATEGI ADAPTASI UMKM DALAM MENGHADAPI PENURUNAN DAYA BELI MASYARAKAT: UPAYA MEMPERTAHANKAN PENDAPATAN DAN LAPANGAN KERJA - Edi Arisandi; Iwan Kusnadi (Adiba Aisha Amira, 2025)
The decline in people's purchasing power has had an impact on the sustainability of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This study aims to identify and analyse the adaptation strategies implemented by MSMEs in facing economic pressures due to declining purchasing power, as well as how these strategies contribute to maintaining income and employment. A literature review method was used by examining various literature, including books, journals, and official reports related to MSMEs, purchasing power dynamics, and business strategy innovations in crisis situations. The results of the study indicate that product innovation, marketing digitalisation, business diversification, operational efficiency, and collaboration among MSME actors are the main strategies that are effective in maintaining business stability and labour absorption. This study also highlights the important role of government support in supporting the success of these adaptation strategies. These findings are expected to serve as a reference for stakeholders in developing more effective policies and programmes to strengthen the resilience of MSMEs in times of economic uncertainty.